Path dependence and regional disparities in single-industry towns in Russia: the evidence from micro data; International Journal of Economic Policy in Emerging Economies; Vol. 16, iss. 2, 3, 4 - Antonova I. S. Irina Sergeevna (2022, 2022)
Title screen